Kyrgyz Republic : Poverty Assessment, Volume 1. Growth, Employment and Poverty - World Bank (Washington, DC, 2012)
This report, which has been prepared by the World Bank in cooperation with the National Statistical Committee, provides an assessment of poverty in the Kyrgyz Republic using the most recent data available. The objective of this report is to understand to what extent economic growth has reduced poverty and led to improved living conditions for the population during 2000-2005. The report also attempts to answer three questions about the Kyrgyz Republic: what is the profile of poor? How has economic growth affected the level and composition of poverty? How has the labor market contributed to changes in poverty? The report is divided into two volumes. The first volume begins with this chapter which provides an international comparison of social and other key indicators of the Kyrgyz Republic followed by a profile of the poor based upon 2005 household survey data. The second chapter analyzes the linkages between growth and poverty during 2000-2005. The third chapter provides our key findings of labor market outcomes and poverty and what the implications are for policy making. The final chapter synthesizes the information from the earlier chapters and provides some policy directions. The second volume provides a more thorough analysis of labor markets. It covers developments in the labor market, urban labor markets, rural labor markets and differences between men and women in the labor market.